2022
DOI: 10.1038/s41598-022-22441-4
|View full text |Cite
|
Sign up to set email alerts
|

A multifunctional ultra-thin acoustic membrane with self-healing properties for adaptive low-frequency noise control

Abstract: This paper proposes a novel multifunctional ultra-thin membrane based on a Polyborosiloxane-based gel with stimuli-responsive sound absorption and sound transmission loss (STL) and characterised by excellent self-healing properties. This adaptive behaviour is the result of a dynamically activated phase transition in the membrane’s polymeric network which is given by the interaction with the travelling sound pressure wave. The presence and the extent of such phase transition in the material was investigated via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…Additionally, the excitation levels of the secondary were selected as such (1.5, 3 and 9 kHz) in order to investigate the effect on the stiffening mechanism of the SSG outside the low frequency range between 300 and 650 Hz. At the lower excitation level of the primary sound source (Figure 7a and LSW = 0.1 V), the evaluated absorption coefficients demonstrated a clear trend observed in similar studies, with a clear shift of these peaks towards lower frequencies [15]. In detail, at the lower frequency range region (352 Hz), α remained virtually unchanged with a shift of frequencies of 10 Hz, whereas the same trend was observed at the higher range (624 Hz), with an approximate α reduction of 10% in this case.…”
Section: Active Systemsupporting
confidence: 79%
See 2 more Smart Citations
“…Additionally, the excitation levels of the secondary were selected as such (1.5, 3 and 9 kHz) in order to investigate the effect on the stiffening mechanism of the SSG outside the low frequency range between 300 and 650 Hz. At the lower excitation level of the primary sound source (Figure 7a and LSW = 0.1 V), the evaluated absorption coefficients demonstrated a clear trend observed in similar studies, with a clear shift of these peaks towards lower frequencies [15]. In detail, at the lower frequency range region (352 Hz), α remained virtually unchanged with a shift of frequencies of 10 Hz, whereas the same trend was observed at the higher range (624 Hz), with an approximate α reduction of 10% in this case.…”
Section: Active Systemsupporting
confidence: 79%
“…The acoustic properties of the material underwent a dynamic change, since these are highly affected by the dynamic transport parameters such as permeability and tortuosity, in addition to morphology of the polymeric network and thermal-dependent parameters [31][32][33]. The uniqueness of each formulation of the SSGs, ought to the PDMS precursor employed and the environmental conditions during the synthesis, appeared to have a direct effect on the position, amplitude and shift of the sound absorption coefficient peaks, when these are compared to previous studies [15].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In previous work 19 , we introduced these SSG based thin-membranes and managed to achieve high absorption coefficients (α > 0.9),in the low frequency range, which dynamically shifted to lower frequencies as the sound wave pressure wave was increased. In our following work we also demonstrated that this behaviour can be actively controlled, by the introduction of a secondary sound source, for applications where active noise control is required 20 .…”
Section: Introductionmentioning
confidence: 99%
“…At low strain rates, SSG exhibits viscous characteristics with increased flowability, as there is sufficient time for the B-O bonds to break [16]. At higher strain rates, the B-O bonds will dynamically break and reconstruct resulting in increased molecular resistance and a high stiffness at the macroscale [19], with this behaviour also resulting in the self-healing performance of SSG [20]. This phase transition, from viscous to rubbery state, is responsible for the excellent energy absorption characteristics of the SSG, with energy consumed in this process.…”
Section: Introductionmentioning
confidence: 99%